Challenges in Implementing Evidence-Based Practices and Programs in Nonprofit Human Service Organizations. Issue 6 (1st November 2016) - Despard, Mathieu R.
Abstract : Evidence-based practice (EBP) is an important, yet under-utilized strategy to improve social work practice. Nonprofit human service organizations (NPHSOs) are a common social work practice setting through which efforts to promote EBP ought to be better understood. NPHSOs experience capacity limitations, lack of access to research evidence, and funding difficulties which makes adopting, implementing, and sustaining EBP challenging, if not untenable. These challenges are more acute for NPHSOs in practice fields for which little top tier intervention research evidence, dissemination platforms, and funding programs exist. Recommendations for overcoming these challenges are discussed.